Kekuatan Genggaman Tangan sebagai Indikator Awal Sarkopenia serta Peran Status Gizi dan Faktor Sosiodemografi - Nurjanah, Hanna; Asanti, Ernis; Utami, Fista (Nutriology : Jurnal Pangan, Gizi, Kesehatan, 2025)
The condition of age-related loss of skeletal muscle mass, accompanied by a decrease in muscle strength and/or physical performance, is defined as sarcopenia. Handgrip strength is an indicator for detecting possible sarcopenia. Nutritional status also plays an important role in influencing handgrip strength. The purpose of this study was to analyze the determinants of sociodemographic factors, nutritional status, and smoking habits on the risk of sarcopenia using handgrip strength as an indicator. This research method uses cross-sectional data from the 2023 Indonesia Longitudinal Aging Survey (ILAS). The research subjects were elderly people aged ≥60 years living in households. Handgrip strength assessed using the 2019 AWGS criteria. The results showed that advanced age, female gender, not working, and nutritional status, are associated with low handgrip strength as an indicator of sarcopenia risk (p < 0.05), while educational level and smoking habits do not show a significant association (p > 0.05). The conclusion is that age, gender, nutritional status, and employment status are important determinants of sarcopenia risk in the elderly. Prevention efforts should focus on adequate nutritional intake and early screening of muscle strength.